The Effect Of Leadership, Organizational Culture, Commitment, And Teacher Competency On Teacher Performance - Satata, Sri; Trisnamansyah, Sutaryat; Sujiarto, Heru; Kosasih, Usep (CV. Inara, 2022)
This study aims to determine: (1) the influence of the principal's leadership on the performance of West Jakarta Senior High School teachers, (2) the influence of organizational culture on the performance of West Jakarta State Senior High School teachers, (3) the influence of organizational commitment on the performance of West Jakarta State Senior High School teachers, (4 ) the influence of teacher competence on teacher performance at SMAN West Jakarta, and (5) the influence of principal leadership, organizational culture, organizational commitment and teacher competence on teacher performance at SMAN West Jakarta. This study uses a descriptive method with a quantitative approach. The population in this study were all teachers at SMAN West Jakarta, totaling 727 teachers, while the sample consisted of 100 teachers from 4 SMAN West Jakarta selected randomly. The research instrument used a Likert scale which was modified into 9 choices, consisting of 49 statement items spread over five research variables. The results of the analysis show (1) the principal's leadership has a positive and significant effect on teacher performance, with a fairly strong level of influence (2) organizational culture has a positive and significant effect on teacher performance, with a fairly strong level of influence (3) organizational commitment has a positive and significant effect on teacher performance. significant effect on teacher performance, with a strong level of influence (4) teacher competence has a positive and significant effect on teacher performance, with a strong level of influence and (5) principal leadership, organizational culture commitment and teacher competence together have a positive and significant effect on teacher performance, with a strong level of influence.